When we can change the sign of denominatorSuppose z = − x 1 x 2...

delirija7z

delirija7z

Answered

2022-07-08

When we can change the sign of denominator
Suppose z = x 1 x 2 x 3 , find z.
Which one is correct z = x 1 x 2 x 3       or       z = x 1 x 2 + x 3

Answer & Explanation

Adolfo Rich

Adolfo Rich

Expert

2022-07-09Added 9 answers

We have z = x 1 x 2 x 3 ,   z = ( 1 ) x 1 x 2 x 3
z = x 1 x 2 x 3 = ( 1 1 ) x 1 x 2 x 3 = ( 1 1 ) x 1 x 2 x 3 = x 1 x 3 x 2
Notice that in one of your proposed solutions above you would find the following:
x 1 x 3 x 2 = ( 1 ) ( x 1 ) ( 1 ) ( x 2 x 3 ) = x 1 x 2 x 3 = z
You may only apply the negative factor to either the numerator or the denominator, but not both because they will negate eachother.

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get your answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?